Prenatal testing and pregnancy termination in Sri Lanka: views of medical students and doctors. - Simpson, B.; Dissanayake, V.H.W.; Wickramasinghe, D.; Jayasekara, R.W. (Sri Lanka Medical Association, 2003)
INTRODUCTION: Prenatal diagnosis and pregnancy termination generate complex ethical issues. Surveys conducted in Sri Lanka among doctors and medical students in 1986 supported a change in law in favour of pregnancy termination when gross genetic defects are detected antenatally. A new generation of prenatal tests has focused attention again on the topic of termination and under what circumstances it might be legally done. The present survey contributes to the debate by means of a survey of doctors and medical students. METHOD: A self-administered questionnaire given to doctors and medical students. RESULTS: Ninety three per cent of doctors and 81% of students accept pregnancy termination as an appropriate course of action if a gross genetic defect is detected antenatally, and 87% of doctors and 80% of students support a change in the law to allow termination of the pregnancy. The corresponding figures in previous surveys were 80%, 69% and 96%, 88% respectively. CONCLUSIONS: A majority of doctors and medical students support a change in law in favour of liberalising pregnancy termination when a genetic defect is detected antenatally.
Keywords: Abortion; ethical issues; genetic disorder